Advances in microbial physiology. - Poole, Robert K. (Academic Press, 2000)
TOPICS COVERED IN THIS VOLUME 1. The molecular genetics of cultivated mushrooms 2. The intestinal microflora: potentially fertile ground for microbial physiologists 3. Primary metabolism and its control in Streptomycetes: a most unusual group of bacteria 4. Acid adaptation in oral Stretococci Key Features * Covers recent advances in microscopical techniques * Applicable to researchers in microscope instrumentation and to users in a range of disciplines, including biology, materials research and development, non-destructive testing, and the electronics service industry.